1983
DOI: 10.3109/00016348309155810
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Ossification Associated with Repeated Abortions

Abstract: Abstract. A patient with repeated abortions and a finding of endometrial ossification is reported. The etiology and pathogenesis of endometrial ossification are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
3

Year Published

1993
1993
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 4 publications
0
18
0
3
Order By: Relevance
“…It has been reported that the time interval between the abortion and osseous metaplasia can range from 8 weeks to 23 years [5,6]. Hysteroscopic or resectoscopic excision of the bones is the mainstay of the treatment [2][3][4][5][6][7][8][9][10][11]. Ultrasonographic or laparoscopic guidance may be applied in extensive osseous metaplasias at which there may be deep myometrial invasion.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the time interval between the abortion and osseous metaplasia can range from 8 weeks to 23 years [5,6]. Hysteroscopic or resectoscopic excision of the bones is the mainstay of the treatment [2][3][4][5][6][7][8][9][10][11]. Ultrasonographic or laparoscopic guidance may be applied in extensive osseous metaplasias at which there may be deep myometrial invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, a pesar de los pocos reportes que ponen énfasis en el tejido óseo residual en el útero, se cree que si no existe tejido óseo en la cavidad endometrial, el tejido óseo residual incrustado en el miometrio no tendría un significado clínico relevante [3][4][5][6][7][15][16][17][18][19][20][21] .…”
Section: Discussionunclassified
“…Sporadic cases without antecedent pregnancy support this theory [9,10,11,12]. Over the past few decades there have been several case reports describing endometrial ossification [13,14,15,16,17]. It is most commonly believed to be due to retained fetal bone fragments, but some cases may be due to metaplasia of mature endometrial stromal cells in response to chronic inflammation or trauma [9].…”
Section: Etiopathologymentioning
confidence: 95%